Nanoscience in food and agriculture. 5 - Ranjan, Shivendu; Dasgupta, Nandita; Lichtfouse, Eric (Springer, 2017)
This book presents comprehensive reviews on the principles, design and applications of nanomaterials in the food and agriculture sectors. This book is the fifth of several volumes on Nanoscience in Food and Agriculture, published in the series Sustainable Agriculture Reviews. Nanotechnology, the use of techniques to create nanomaterials, is a rapidly emerging scientific field. Yet nanomaterials are nothing new; they have always occurred in nature. What is new: the methods that allow us to synthesize unprecedented nanomaterials with precisely tailored properties, thus opening the door for many applications in diverse fields. In particular, the high surface to volume ratio of engineered nanomaterials makes them often more efficient than their natural equivalents. Surprisingly, some nanomaterials even exhibit contrasting properties compared to their macro counterparts. While nanomaterials have been widely commercialized in various sectors, their use in food industries is still slowly emerging and hotly debated. Findings show that nanomaterials can improve bioavailability and shelf life. Further, by reducing nutrient loss, they are essential to active packaging: packaging systems that help to extend shelf life, monitor freshness, display information on quality, and improve safety and convenience. Nevertheless, the potential toxicity of new nanomaterials should be studied before their use in consumer products.
Keywords: Food industry and trade -- Technological innovations.; Nanotechnology.; Agricultural innovations.; elektronické knihy; electronic books